The effects of persistent audible seat belt reminders and a speed-limiting interlock on the seat belt use of drivers who do not always use a seat belt. (December 2019) - Kidd, David G.; Singer, Jeremiah
Highlights: Belt use of 81 part-time belt users was recorded for 2 weeks in 2 studies. Part-time users experienced a persistent belt reminder or a belt interlock system. Persistent belt reminders increased belt use of part-time users by 30–34%. Restricting speed or gear selection increased belt use rate by 16–33%. Reminders that increase belt use 34% would save an estimated 1, 489 lives annually. Abstract: Introduction : Vehicle technologies that increase seat belt use can save thousands of lives each year. Kidd, Singer, Huey, and Kerfoot (2018) found that a gearshift interlock was more effective for increasing seat belt use than an intermittent audible reminder, but interlocks may not be more effective than persistent audible reminders lasting at least 90 seconds. Method : Forty-nine part-time belt users with a recent seat belt citation who self-reported not always using a seat belt drove two vehicles for 1 week each. Thirty-three drove a Chevrolet with an intermittent audible reminder followed by either a BMW with a persistent 90-second audible reminder ( n  = 17) or a Subaru with an incessant audible reminder ( n  = 16). The other 16 participants experienced the BMW persistent reminder followed by an interlock that limited speed to 15 mph during unbelted driving. These data were combined with data from 32 part-time belt users in Kidd et al. (2018) who experienced the intermittent reminder for 2 weeks or the intermittent reminder for 1 week and a gearshift interlock the next. Results : Relative to the intermittent reminder, seat belt use was significantly increased an estimated 30% by the BMW persistent reminder, 34% by the Subaru incessant reminder, and 33% by the speed-limiting interlock. Belt use was increased an estimated 16% by the gearshift interlock, but this change was not significant. More participants circumvented the speed-limiting interlock to drive unbelted than the audible reminders. Responses to a poststudy survey indicated that interlocks were less acceptable than reminders. Conclusions : Audible reminders lasting at least 90 seconds and a speed-limiting interlock were more effective for increasing seat belt use than an intermittent audible reminder, but reminders were found more acceptable. Practical applications : Strengthening existing U.S. safety standards to require audible reminders lasting at least 90 seconds for front-row occupants could save up to 1, 489 lives annually.